Anatomy of the Nasal and Auditory Regions of the Fossil Lagomorph Palaeolagus haydeni: Systematic and Evolutionary Implications - Ruf, Irina; Meng, Jin; Fostowicz-Frelik, Łucja (Frontiers in Ecology and Evolution, 2021)
Palaeolagus, a late Eocene to early Miocene North American lagomorph genus, represented by numerous and well-preserved specimens, has been long considered a basal leporid, although it is currently understood as a stem lagomorph. Based on micro-computed tomography (µCT) data and 3D reconstructions, here we present the first description of intracranial structures of the nasal and auditory regions of a complete skull of Palaeolagus haydeni from the early Oligocene of Nebraska. Although Palaeolagus haydeni shows a puzzling mixture of extant leporid and ochotonid characters, it helps to polarize and re-evaluate already known lagomorph intracranial characters based on outgroup comparison with Rodentia and Scandentia. Common derived features of Palaeolagus haydeni and extant Lagomorpha are the dendritic maxilloturbinal and the excavated nasoturbinal that contacts the lamina semicircularis. Generally, Palaeolagus haydeni and Leporidae have several characters in common, some of which are certainly plesiomorphic (e.g., thin wall of bulla tympani and flat conic cochlea). Palaeolagus haydeni resembles Leporidae in having an interturbinal between the two frontoturbinals, and three ethmoturbinals plus one interturbinal between ethmoturbinal I and II. Now, this should also be regarded as a plesiomorphic grundplan pattern for Leporidae whereas ochotonids are derived from the lagomorph grundplan as concerns the number of frontoturbinals. Concerning the middle ear, Palaeolagus haydeni significantly contributes to the polarization of the anterior anchoring of the malleus in extant lagomorphs. Palaeolagus haydeni resembles the pattern observed in early ontogenetic stages of Ochotonidae, i.e., the attachment of the malleus to the ectotympanic via a short processus anterior. The patterns in adult ochotonids and leporids now can be regarded as two different and apomorphic character states. Autapomorphic characters of Palaeolagus haydeni are the reduced frontoturbinal 2 and the additional anterolaterally oriented process of the lamina semicircularis. Interestingly, among the investigated intracranial structures the loss of the secondary crus commune is the only apomorphic grundplan character of crown Lagomorpha.